2022
DOI: 10.17517/ksutfd.885827
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Mental Health Status, Fatigue and Sleep Quality in Nursing Students: A Cross-Sectional Study

Abstract: Amaç: Bu çalışma hemşirelik öğrencilerinin ruhsal sağlık, yorgunlukve uyku kaliteleri arasındaki ilişkiyi ve etkileyen faktörleri belirlemek amacı ile yapılmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In a study conducted by Hacıalioğlu et al (2019) general health was found to be at higher risk for mental diseases in first graders. In other studies, it was reported that grade levels did not affect general health (Nazik & Dişli, 2022;Uysal & Yenal, 2014). The general health levels of the other classes, except the first year, might have been higher…”
Section: General Health Questionnaire-12mentioning
confidence: 89%
See 2 more Smart Citations
“…In a study conducted by Hacıalioğlu et al (2019) general health was found to be at higher risk for mental diseases in first graders. In other studies, it was reported that grade levels did not affect general health (Nazik & Dişli, 2022;Uysal & Yenal, 2014). The general health levels of the other classes, except the first year, might have been higher…”
Section: General Health Questionnaire-12mentioning
confidence: 89%
“…were in the psychological risk group (Nazik & Dişli, 2022), and 31.1% were at risk of depression (Özkan & Yilmaz, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancak her zaman belirli nedenlere bağlı olarak uyku için bu süre sağlanmayabilmektedir (Yorulmaz ve ark., 2018). Buna paralel olarak da kişinin uyandıktan sonra dinlenmiş ve zinde olmasını tanımlayan uyku kalitesinde bozulma ya da uyku bozuklukları görülebilmektedir (Nazik & Dişli, 2022). Uyku bozuklukları yaş, cinsiyet, çevresel ve genetik faktörler ve sosyal yaşam gibi birçok duruma bağlı olarak ortaya çıkmaktadır (Ekenler & Altınel, 2021).…”
Section: Introductionunclassified